2016
DOI: 10.1002/tcr.201600002
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Copper(I)-Catalyzed Azide-Alkyne Cycloaddition

Abstract: The copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) reaction regiospecifically produces 1,4-disubstituted-1,2,3-triazole molecules. This heterocycle formation chemistry has high tolerance to reaction conditions and substrate structures. Therefore, it has been practiced not only within, but also far beyond the area of heterocyclic chemistry. Herein, the mechanistic understanding of CuAAC is summarized, with a particular emphasis on the significance of copper/azide interactions. Our analysis concludes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 92 publications
(146 reference statements)
2
70
0
Order By: Relevance
“…, cysteine) prevented quenching but also prevented any measurable CuAAC coupling, suggesting charged ligands can prevent Cu + from reaching the nanocrystal surface but may also inhibit interaction with the alkyne. 21, 3637 Two triazole-based ligands (THPTA and BTTAA) proved most effective at generating Cy5 FRET emission while ameliorating quenching (Table S1), and optimization with THPTA gave us a FRET spectrum most similar to that of the QD-Cy5 conjugate synthesized without Cu (Figure 3b). Previous work has shown that BTTAA is superior to other Cu ligands for promoting CuAAC coupling with hydrophobic substrates, 33, 4546 while in this case the QD surfaces and Cy5 are both hydrophilic, possibly explaining the differences seen here.…”
Section: Resultsmentioning
confidence: 99%
“…, cysteine) prevented quenching but also prevented any measurable CuAAC coupling, suggesting charged ligands can prevent Cu + from reaching the nanocrystal surface but may also inhibit interaction with the alkyne. 21, 3637 Two triazole-based ligands (THPTA and BTTAA) proved most effective at generating Cy5 FRET emission while ameliorating quenching (Table S1), and optimization with THPTA gave us a FRET spectrum most similar to that of the QD-Cy5 conjugate synthesized without Cu (Figure 3b). Previous work has shown that BTTAA is superior to other Cu ligands for promoting CuAAC coupling with hydrophobic substrates, 33, 4546 while in this case the QD surfaces and Cy5 are both hydrophilic, possibly explaining the differences seen here.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, current mechanistic studies suggest that both oxidation of Cu(I) by O 2 and CuAAC reactions involve a bi-nuclear copper intermediate. 35, 63, 64 …”
Section: Resultsmentioning
confidence: 99%
“…6470 The di-Cu(I)-acetylide has been proven as a much more active intermediate in the CuAAC reaction than the mono-Cu(I) species. 63 Recently, results of our kinetic study of CuAAC reaction promoted by tris(triazoylmethl)amine ligands indicated the possibility that the trinuclear acelylide-Cu 3 -ligand complexes might be active intermediates in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Binuclear Cu(I) species possess an enhanced reactivity toward organic azides in copper-catalysed azide-alkyne cycloaddition compared to monomeric copper complexes [28][29][30][31][32][33][34][35]. Copper(I) tetrahydroborates with phosphine ligands featuring relative stability to air oxygen and moisture are used as selective reducing agents [36][37][38][39][40], catalysts of photosensitized isomerization of dienes [41][42][43] and hydrolytic dehydrogenation of ammonia borane [44].…”
Section: Introductionmentioning
confidence: 99%
“…Many examples The Cu(I)-dppm complexes are emerging class of polynuclear complexes, that are drawing considerable attention because of their photophysical properties [19][20][21][22] and prospective use as a catalyst [23][24][25] and a sensor for various organic bases [26] and anions [27]. Binuclear Cu(I) species possess an enhanced reactivity toward organic azides in copper-catalysed azide-alkyne cycloaddition compared to monomeric copper complexes [28][29][30][31][32][33][34][35]. Copper(I) tetrahydroborates with phosphine ligands featuring relative stability to air oxygen and moisture are used as selective reducing agents [36][37][38][39][40], catalysts of photosensitized isomerization of dienes [41][42][43] and hydrolytic dehydrogenation of ammonia borane [44].…”
Section: Introductionmentioning
confidence: 99%